2022
DOI: 10.3389/fmicb.2022.884374
|View full text |Cite
|
Sign up to set email alerts
|

Unique Reciprocal Association Seen Between Latent Tuberculosis Infection and Diabetes Is Due to Immunoendocrine Modulation (DM-LTB-1)

Abstract: AimThe prevalence of latent tuberculosis infection (LTBI) among diabetes patients is poorly studied. In the present study, the prevalence of LTBI among pre-diabetes and diabetes patients was studied, along with immunoendocrine biomarkers (n = 804).MethodsLTBI was screened by Quantiferon TB gold in Normal glucose tolerance [(NGT); n = 170, [Pre-diabetes (PDM; n = 209), Newly diagnosed diabetes (NDM; n = 165) and Known diabetes (KDM; n = 260) subjects. CRP, TNF-α, IL-6, IL-1β, IFN-β, IL-12, IFN-γ, IL-2, insulin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…Further, with respect to diabetes, most studies have been carried out only in chronic diabetes subjects, and what happens during the pre- and incipient of diabetes, is still an enigma ( 4 , 18 ). Recently, we carried out LTBI screening, among individuals with various grades of increasing glucose intolerance ( 19 ). We found a decreased prevalence of LTB among pre-diabetes (23%) and newly diagnosed diabetes patients (23%), compared to healthy controls (33%) and chronic diabetes patients (33%) ( 19 ).…”
Section: Antagonistic Relationship Between Ir and Ltbimentioning
confidence: 99%
See 3 more Smart Citations
“…Further, with respect to diabetes, most studies have been carried out only in chronic diabetes subjects, and what happens during the pre- and incipient of diabetes, is still an enigma ( 4 , 18 ). Recently, we carried out LTBI screening, among individuals with various grades of increasing glucose intolerance ( 19 ). We found a decreased prevalence of LTB among pre-diabetes (23%) and newly diagnosed diabetes patients (23%), compared to healthy controls (33%) and chronic diabetes patients (33%) ( 19 ).…”
Section: Antagonistic Relationship Between Ir and Ltbimentioning
confidence: 99%
“…Recently, we carried out LTBI screening, among individuals with various grades of increasing glucose intolerance ( 19 ). We found a decreased prevalence of LTB among pre-diabetes (23%) and newly diagnosed diabetes patients (23%), compared to healthy controls (33%) and chronic diabetes patients (33%) ( 19 ). It is important to note that gender plays an important role in disease susceptibility towards both diabetes as well as LTB.…”
Section: Antagonistic Relationship Between Ir and Ltbimentioning
confidence: 99%
See 2 more Smart Citations
“…These findings clearly reveal that due to metabolic dysfunction, an imbalance in the appearance of pro- and anti- inflammatory adipocytokines arises in TB-DM, which is an important feature that could influence the development of TB pathogenesis ( 63 ). There was a study by Aravindhan V et al., who have shown that inflammatory markers such as IL-1β, IFNγ and adiponectin were significantly elevated in LTBI individuals with newly diagnosed DM (NDM) in comparison to LTBI negative individuals with NDM ( 64 ). Subsequently from the same group, another study demonstrated that there was elevated IL-27 and IL-10 levels in the LTBI NDM, compared to LTBI group ( 65 ).…”
Section: Immune Biomarkers To Ltbi Individuals With Dmmentioning
confidence: 99%